2021
DOI: 10.1186/s12944-021-01475-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of ST-segment elevation myocardial infarction (STEMI) patients using machine learning based on lipid profiles

Abstract: Background Numerous studies have revealed the relationship between lipid expression and increased cardiovascular risk in ST-segment elevation myocardial infarction (STEMI) patients. Nevertheless, few investigations have focused on the risk stratification of STEMI patients using machine learning algorithms. Methods A total of 1355 STEMI patients who underwent percutaneous coronary intervention were enrolled in this study during 2015–2018. Unsupervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Recently, a machine learning-based clustering study among patients with STEMI under statin therapy evaluated a lipid panel composed of apo A1, Apo B, HDL-C, triglycerides, LDL-C, total cholesterol and lipoprotein (a) [Lp (a)]. The study revealed that the cluster with high levels of Lp (a) and low levels of apoA1 and HDL-C identified those patients with the highest recurrent events and mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a machine learning-based clustering study among patients with STEMI under statin therapy evaluated a lipid panel composed of apo A1, Apo B, HDL-C, triglycerides, LDL-C, total cholesterol and lipoprotein (a) [Lp (a)]. The study revealed that the cluster with high levels of Lp (a) and low levels of apoA1 and HDL-C identified those patients with the highest recurrent events and mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can search for similarities and heterogeneities among large categories of data variables and isolate them into clinically meaningful clusters [8,[15][16][17]. Recent studies have shown that disease subtypes determined by ML clustering methods can forecast different clinical outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Consensus clustering is an unsupervised ML approach utilized to identify distinct phenotypes in heterogeneous patient populations. It can be used to assess similarities and differences in large datasets with many variables, and subsequently distinguish patients into novel clusters with distinct phenotypes [12,15,16]. Recent studies have demonstrated that ML consensus clustering can identify disease subtypes that carry different clinical outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%